Factors Associated with Sexual Intercourse Frequency Among South African Women: Evidence from a National Cross-sectional Survey - Tshaudi Motsima (Journal of Psychosexual Health)
Background: Engaging in regular healthy sexual intercourse activities is good for human health and well-being. Greater sexual intercourse frequency (SIF) for people in relationships is often associated with well-being, greater relationship satisfaction, reduced mortality, increased life expectancy, positive emotions and happiness, while lack of sexual activity is usually associated with depression and marital disharmony. Aim: The primary purpose of this study is to identify the factors associated with SIF among women in South Africa. Data and Methods: The South African Demographic and Health Survey 2016 data were used, and the negative binomial regression model (NBRM) was employed for analysis. Results: Age was significantly associated with high SIF (IRR = 1.02; p < .001). African women had significantly higher SIF than Indian/Asian women (IRR = 1.28; p = .049). Married women had a significantly higher SIF than women who were never married (IRR = 1.42; p < .001). Women who resided in urban areas were significantly associated with higher SIF than women who resided in rural areas (IRR = 1.14; p < .001). Conclusion: Being young, being Indian/Asian, being unmarried, and residing in rural areas is associated with low SIF, whereas being older, being African, being married, and staying in urban areas is associated with high SIF. Generally, without violating cultural, religious and societal beliefs, married women should be taught about the benefits of sexual intercourse activity (SIA) and be encouraged not to be ashamed of entering into sexual intercourse activities.